Macroeconomic effects of the current crises in Japan and MENA countries - A model-based assessment of the medium term - Anke Mönnig; Kirsten Wiebe (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2011)
Two events currently preoccupy global news: the political unrest in the Middle East and North Africa (MENA) and the earthquake, tsunami and nuclear catastrophe in Japan. Both events are very different in its nature and location, but they not only affect economic developments within these countries but also across the world. In the current paper, the macroeconomic effects of both events and of a combination of both crises are analysed by applying a dynamic interindustry model. That not only allows to estimate the impact on other economies in the year of the crisis but also to consider the adjustment process in the preceding years. Overall, the analysis has shown that Japans natural disaster is likely to have hardly any effects on the world economy in general and its major trading partners in particular. Moreover, the long-run effects function like a stimulation package to the economy. On the contrary, the macroeconomic effects of a reduction in oil production due to the political disruption in the MENA countries are considerable and depend on country specifics concerning energy intensity, trade relations or degree of industrialization and energy efficiency. In conclusion, the analysis shows that the world economy heavily reacts on sudden world oil price changes but is less vulnerable to ad-hoc production shortages of leading industrial economies.
Keywords: O53; 330; Crises; world economy; dynamic interindustry model; Wirtschaftskrise; Investition; Makroökonomischer Einfluss; Japan; Erdölgewinnung; Politische Unruhen; Ölpreis; Makroökonomischer Einfluss; Welt